Pre-school teacher’s perceived self-efficacy on implementation of national early childhood curriculum: implications for the achievement of sustainable development goal on education in Nigeria (2019)
The early years are critical in the life of every child as experiences gained during the period can have lasting effects on the child. For this reason, programmes aimed atfostering proper stimulations and holistic development ofthe child are usually put in place. One of such programmes is Early Childhood Education (ECE) which is guided by a curriculum in order to achieve the set objectives of the programme. For this reason, the Nigerian Government developed the National Early Childhood Education Curriculum for Ages 0-5 years. It is however not known whether pre-school teachers have the self- efficacy to effectively implement this curriculum. This study thus investigated Pre-School Teachers Perceived Self- Efficacy on Implementation of the National Early Childhood Education Curriculum for Ages 0-5 years in Ondo West Local Government Area of Ondo State. The study adopted survey research design. Purposive sampling technique was used in selecting twenty five (25) public and thirty five (35) private primary schools'in the study area making a total ofsixty (60) primary schools. “Questionnaire on Pre-school Teachers' Perceived Self-efficacy on Implementation ofthe National Early Childhood Curriculum (QPTPSNECC) ” was the instrument used. Data collected were analysed using percentage, mean and standard deviation while T-test was used to test the hypothesis raised. Findings revealed that pre-service teachers self- efficacy on the implementation Childhood Curriculum for Ages 0-5 years was average. These findings have serious implications for the country's attainment of Sustainable Development Goal 4.2. It was recommended that pre-school teachers should be made to regularly attend trainings that will enable them acquire necessary skills for effective implementation of the curriculum.